2020
DOI: 10.1016/j.hroo.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial distance predicts the necessity of additional carina ablation to isolate the right-sided pulmonary veins

Abstract: BACKGROUND Ablation of the pulmonary vein (PV) carina is occasionally required for PV isolation (PVI). Marshall bundle and epicardial connections between the right-sided PV (RtPV) carina and right atrium (RA) may be one of the mechanisms that necessitates carina ablation.OBJECTIVE We sought to clarify anatomical characteristics predictive of the necessity of carina ablation.METHODS Forty-five consecutive patients undergoing radiofrequency catheter ablation of atrial fibrillation were prospectively included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 19 publications
4
21
3
Order By: Relevance
“… 7 , 8 , 9 Therefore data referring to electrical and anatomical characteristics of the carina region have been published recently. 10 , 11 In our present study, we observed frequency and distribution of carina‐related PV conduction after encircling of ipsilateral PVs during PVI. Furthermore, we hypothesized that carina width can be measured utilizing a fast anatomical mapping (FAM) of the LA and its conjunctive PV, which is generated routinely during PVI.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“… 7 , 8 , 9 Therefore data referring to electrical and anatomical characteristics of the carina region have been published recently. 10 , 11 In our present study, we observed frequency and distribution of carina‐related PV conduction after encircling of ipsilateral PVs during PVI. Furthermore, we hypothesized that carina width can be measured utilizing a fast anatomical mapping (FAM) of the LA and its conjunctive PV, which is generated routinely during PVI.…”
Section: Introductionsupporting
confidence: 54%
“…Several studies have hinted toward a role of the intervenous carina for persistent conduction between pulmonary veins (PV) and the left atrium (LA) due to an epicardial connection between the carina region and both atria 7‐9 . Therefore data referring to electrical and anatomical characteristics of the carina region have been published recently 10‐11 . In our present study, we observed frequency and distribution of carina‐related PV conduction after encircling of ipsilateral PVs during PVI.…”
Section: Introductionsupporting
confidence: 52%
“…Patel et al 6 electrophysiologically provided a proof of this EC in their case series, which demonstrated electrical isolation of right‐sided PVs by ablation at the RA posterior wall. Recently, we added novel electrophysiological and anatomical analyses advancing this suggestion and interpretation 7,9 . The presence of a conduction breakthrough at the carina region during SR highly predicted the necessity of carina ablation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency energy was delivered at a power of 25–35 W at the posterior aspect, at 15–20 W at the sites adjacent to the esophagus, and at 30 to 40 W at the anterior aspect of the PV antrum. Target values of the ablation index (Biosense‐Webster) were 500 for the anterior aspect and 400 for the posterior aspect of the PV antrum, and the inter‐lesion distance was 4 mm 8,9 . PVI with entrance and exit blocks was confirmed with the Lasso catheter and a pacing maneuver within the isolation line with an ablation catheter 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary vein (PV) isolation is widely applicable as an effective treatment for atrial fibrillation (AF). Electrophysiologists occasionally encounter right-sided PVs (RtPVs) that are difficult to isolate without ablation in the PV carinal area, thus suggesting the presence of an epicardial connection (EC) between the RtPV carina and the right atrium (RA) ( 1 , 2 , 3 , 4 , 5 , 6 , 7 ).
Learning Objectives
To recognize IAC injuries in patients with atrial remodeling associated with AF.
…”
mentioning
confidence: 99%